2014
DOI: 10.1016/j.ijme.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The international business of higher education – A managerial perspective on the internationalisation of UK universities

Abstract: (2014) 'The international business of higher education a managerial perspective on the internationalisation of UK universities.', International journal of management education., 12 (2). pp. 91-103. Further information on publisher's website:http://dx.doi.org/10.1016/j.ijme.2014.02.003Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in The International Journal of Management Education. Changes resulting from the publishing process, such as pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
(50 reference statements)
1
29
0
3
Order By: Relevance
“…The findings of the study demonstrate a range of concerns with respect to lowered student engagement, falling academic standards and increasing pressure and stress amongst academic staff. It is clear that the current model of consumerisation focuses on financial stability and success, which is ill at ease with the traditional view and purpose of HEIs (Meek 2000;Warwick 2014). Consistent with these views, our findings provide insights into extant academics' perceptions of the impact of the consumerist shift on a range of HEI stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study demonstrate a range of concerns with respect to lowered student engagement, falling academic standards and increasing pressure and stress amongst academic staff. It is clear that the current model of consumerisation focuses on financial stability and success, which is ill at ease with the traditional view and purpose of HEIs (Meek 2000;Warwick 2014). Consistent with these views, our findings provide insights into extant academics' perceptions of the impact of the consumerist shift on a range of HEI stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…International partnerships make it possible for the HEIs to improve on the quality of their academic and research programmes and internationalise their curriculum, thereby increasing patronage and improving their status in the academic and industrial environment, locally and internationally (Ho, 2017;Warwick, 2014). HEIs are motivated by access to knowledge for research, since localised knowledge is not enough to make the conclusions that research findings are applicable internationally (Costa, Soares, & de Sousa, 2016).…”
Section: Academic Motivesmentioning
confidence: 99%
“…Specifically, studies conducted by Morris and Laipple, 2015 in U.S. showed that the wellness of staff behaviour are increased effectively through the development of leadership capacities of school or university executives as well as the well-established working systems for the leaders to perform their tasks [30]. With regard to those capacities, for the survival of the university organizations in the U.K., the findings of Warwick (2014) indicated that international strategic capacities were identified by most universities as important elements in improving their performance in the global competition in the future [31].…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%